RP-HPLC Analysis of 6-Gingerol and Assessment of Antioxidant Activities in EMS Treated Ginger - Sandeep Pai, Firdose Kolar and Ghansham Dixit, Nilesh Pawar, Mansingraj Nimbalkar (Journal of Phytology, 2010)
<span style="font-size: 10pt; line-height: 110%; font-family: ";Book Antiqua";,";serif";; mso-fareast-font-family: SimSun; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;">Present investigation deals with RP-HPLC analysis of 6- gingerol from rhizome of ginger treated with EMS at different concentrations. The concentration levels were 0.10, 0.15, 0.20 and 0.25% for EMS 8 hour treatment and 0.30, 0.40, 0.50 and 0.60% for 4 hour treatment. The antioxidant activity of extracts were assessed by DPPH radical scavenging method and FRAP. Total phenolic content was determined using the Folin–Ciocalteu (F– C) method. The results showed that the 6- gingerol content increased with an increase in EMS dose initially (0.30%) and decreased at the higher dose (0.60%) in EMS 4 hrs treatments while there was no definite trend observed in EMS 8 hrs treatments. Antioxidant activity and the total phenolic content showed significant correlation with 6-gingerol content.